1999
DOI: 10.1038/sj.onc.1202867
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus X mutants, present in hepatocellular carcinoma tissue abrogate both the antiproliferative and transactivation effects of HBx

Abstract: Chronic infection by HBV is the leading cause of hepatocellular carcinoma in man. Several lines of evidence suggest that the viral transactivator HBx plays a critical role in the molecular pathogenesis of HBVrelated HCC. To study the actual impact of HBx and the mechanism of its action, we have recently cloned and characterized a set of X-sequences from HCC in patients with chronic infection by HBV. In the present study, we have compared the e ects of HBx and its naturally arising mutants on cell growth and vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
154
1
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 190 publications
(177 citation statements)
references
References 58 publications
21
154
1
1
Order By: Relevance
“…Ours and other previous findings have shown that different domains at HBx-COOH may represent various mechanisms, and the mutations may directly affect the proliferation and invasion by regulating the cell cycle and inducing the expression of p21 WAF1 , p14 ARF and MDM2 (13). This supports the hypothesis that deleted forms of HBx may contribute to liver carcinogenesis (13,(30)(31)(32). Our previous findings also demonstrated that CENP-A overexpression was correlated with serum HBsAg states in HCC patients (16).…”
Section: Discussionsupporting
confidence: 74%
“…Ours and other previous findings have shown that different domains at HBx-COOH may represent various mechanisms, and the mutations may directly affect the proliferation and invasion by regulating the cell cycle and inducing the expression of p21 WAF1 , p14 ARF and MDM2 (13). This supports the hypothesis that deleted forms of HBx may contribute to liver carcinogenesis (13,(30)(31)(32). Our previous findings also demonstrated that CENP-A overexpression was correlated with serum HBsAg states in HCC patients (16).…”
Section: Discussionsupporting
confidence: 74%
“…Moreover, HBx deregulates cell cycle check point controls and blocks p53-mediated apoptosis (Lucito and Schneider, 1992;Feitelson et al, 1993;Bennett et al, 1995;Wang et al, 1995;Miura et al, 1997;Chan and Ng, 2006). Interestingly, tumorderived HBx mutants that lacked their transcriptional cotransactivation activity as well as proapoptotic activity (Sirma et al, 1999), still retained their p53-binding functions and blocked p53-mediated apoptosis (Huo et al, 2001. (Figure 6) Furthermore, by losing the proapoptotic ability, the mutant HBx enhanced the transforming ability of ras and myc (Tu et al, 2001).…”
Section: Tp53 Mutations and Hcc Sp Hussain Et Almentioning
confidence: 99%
“…Indeed, codon 94 (nt 1653 to 1655) is within the function domain of the X protein, which has been reported to play a central role in transactivation (Kumar et al, 1996). And the C1653T mutation might enhance the binding affinity of related factors and enhancer II/core promoter activity, cause activation of an indolent immune response, as well as abrogates both the antiproliferative and transactivation effects of wildtype HBx (Lee et al, 1998;Sirma et al, 1999).These changes may be involved in hepatocarcinogenesis.…”
Section: Discussionmentioning
confidence: 99%